PENGARUH KARAKTERISTIK DEWAN DIREKSI TERHADAP KINERJA KEUANGAN YANG DIMODERASI OLEH BANK SIZE DI INDONESIA - Nazmia Widiputri; Nesiya Disman; Farah Margaretha Leon (MANAJEMEN DEWANTARA, 2026)
This study analyzes the influence of board of directors’ characteristics on the financial performance of banks in Indonesia, considering the moderating role of bank size and control variables such as gross domestic product and liquidity risk rasio. The study using a quantitative approach and panel data from 21 commercial banks listed on the Indonesia Stock Exchange for the period 2019–2023, analysis used panel data regression techniques. The findings reveal that bank size and liquidity risk ratio have a significant positive effect on financial performance, measured by return on assets (ROA) and return on equity (ROE). However, board characteristics such as board size, board independence, board gender diversity, and board age diversity do not significantly influence financial performance, nor do their interaction terms with bank size or gross domestic product. Implication for bank management is the importance of focusing on bank size and liquidity risk rasio management to improve profitability, while the role of board characteristics requires further investigation.